Sustainable Construction of Future: Opportunities and Challenges for Green and Buildings - Alaloul, Wesam Salah; Tayeh, Bassam A.; Musarat, Muhammad (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The construction industry is growing rapidly and time has changed the construction methods used. The traditional way of construction is becoming obsolete and technology is taking over. In this case, sustainable construction is the future and the new norm in the construction industry. Although there are various opportunities in this sector, there are also some challenges that exist and hinder productivity. Hence, this reprint covers the opportunities and challenges in sustainable construction.